2016
DOI: 10.1002/mabi.201500347
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Biofilm Inhibition Effects of Acetate‐Buffered Chitosan Sponge Delivery Device

Abstract: Polymicrobial biofilm-associated implant infections present a challenging clinical problem. Through modifications of lyophilized chitosan sponges, degradable drug delivery devices for antibiotic solution have been fabricated for prevention and treatment of contaminated musculoskeletal wounds. Elution of amikacin, vancomycin, or a combination of both follows a burst release pattern with vancomycin released above minimum inhibitory concentration for Staphylococcus aureus for 72 h and amikacin released above inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…Sponges for local and rapid treatment of osteomyelitis appears to be a growing area of interest, particularly in military applications, as they are readily available to pack into traumatic wounds and rapidly deliver therapeutics directly to the site of infection. 29 Reported materials of sponges include chitosan, chitosan-polycaprolactone blends, and collagen, which have been used to deliver gentamicin, 116,152 ciprofloxacin, 29,153 amikacin, 154,155 vancomycin, [154][155][156] rifampin, 29 and others. 157 In two comparative studies in humans, gentamicin loaded collagen sponges matched the efficacy of traditionally used PMMA beads in osteomyelitis treatment, while reducing the need for secondary surgical procedures.…”
Section: Spongesmentioning
confidence: 99%
“…Sponges for local and rapid treatment of osteomyelitis appears to be a growing area of interest, particularly in military applications, as they are readily available to pack into traumatic wounds and rapidly deliver therapeutics directly to the site of infection. 29 Reported materials of sponges include chitosan, chitosan-polycaprolactone blends, and collagen, which have been used to deliver gentamicin, 116,152 ciprofloxacin, 29,153 amikacin, 154,155 vancomycin, [154][155][156] rifampin, 29 and others. 157 In two comparative studies in humans, gentamicin loaded collagen sponges matched the efficacy of traditionally used PMMA beads in osteomyelitis treatment, while reducing the need for secondary surgical procedures.…”
Section: Spongesmentioning
confidence: 99%
“…The combination of two principles of drug loading, (a) drug incorporation within the fiber scaffold and (b) liquid-loading of the PFS pore-system with drug solutions, can turn them into versatile multi-drug carriers that can flexibly provide user-adjustable doses and drug combinations at the point-of-care ( Jennings et al, 2016 ; Parker et al, 2015 ). The fundamental processes prevailing inside of PFS, including liquid-uptake/loading and release mechanisms from the scaffold, are still hardly understood.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a strong interest in local antibiotic delivery mechanisms by direct local application of antibiotic powders or via antibiotic carriers that allow a slower release of antibiotic over time is gaining in popularity [ 10 16 ]. Previous animal studies have shown that commercially available absorbable chitosan sponges are suitable carriers for single-agent antibiotic delivery and allow for reductions in bacteria with or without negative pressure wound therapy adjuncts when applied to a contaminated wound [ 10 , 17 ]. These bioabsorbable chitosan sponges are capable of time-releasing antibiotics directly into a wound bed while also acting as a space filler [ 10 , 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous animal studies have shown that commercially available absorbable chitosan sponges are suitable carriers for single-agent antibiotic delivery and allow for reductions in bacteria with or without negative pressure wound therapy adjuncts when applied to a contaminated wound [ 10 , 17 ]. These bioabsorbable chitosan sponges are capable of time-releasing antibiotics directly into a wound bed while also acting as a space filler [ 10 , 17 20 ]. However, many traumatic orthopedic wound infections are polymicrobial and may require multiple antibiotics for adequate treatment.…”
Section: Introductionmentioning
confidence: 99%